The Process of Music Creation Kelabu | Proses Kreasi Musik “Kelabu” - I Gede Adi Surya; Saptono Saptono; I Ketut Partha (GHURNITA: Jurnal Seni Karawitan, 2022)
This article discusses the process of creating the musical work “Kelabu”, which in its creation uses an experimental stage with orientation to contemporary phenomena. The current phenomenon in question is a situation that leads to a lack of clarity between the news and the truth about the Covid-19 virus that is obtained by the public. This phenomenon then stimulates the stylist to work on the element of obscurity, where the element of ambiguity that the stylist wants to work on tries to find it through an experimental process by applying the use of masks to Balinese drum instruments. The writing of this article aims to provide information about the achievements found in the production of this work, where it is expected to be a motivation and reference in the search for new types of music whose cultivation is oriented to contemporary phenomena. In cultivating the musical work "Kelabu" the stylist uses the creation method of Roger Sessions in collaboration with the creation method of Alma M. Hawkins, so that a new method is obtained which consists of the stages of inspiration, exploration, improvisation and execution. In the experimental process in the production of this work, the stylist found a new sound character on the drum instrument that was not as clear as the conventional drum sound, where the new sound character was caused by the effect of using a mask on the drum instrument.